Optimalisasi Penerapan Penyanderaan (Gijzeling) sebagai Upaya Penegakan Hukum (Law Enforcement) dalam Penerimaan Pajak (Studi Kasus Pelaksanaan Penyanderaan Di Kantor Wilayah Direktorat Jenderal Pajak Sumatera Utara I) - Angreni Fajrin Dalimunthe; Budiman Ginting; Sunarmi; Utary Maharany Barus (Universitas Medan Area, 2022)
This research focuses on Optimizing the Implementation of Hostage Taking (Gijzeling) as an Effort to Enforce Law in Tax Revenue (Case Study of Taxpayer Hostage Taking in Regional Office I of the Directorate General of Taxes, North Sumatra Province). The research method used in this study is normative legal research or doctrinal legal research. This research is descriptive with qualitative data analysis methods. The results of the study indicate that the hostage taking (Gijzeling) at the Regional Office I of the Directorate General of Taxes of North Sumatra Province has been carried out in accordance with statutory regulations, namely the Provision of Compensation in terms of Tax Collection by Warrant juncto Regulation of the Directorate General of Taxes Number PER-03/PJ/ 2018 concerning Amendment to the Decree of the Directorate General of Taxes Number KEP-218/PJ/2003 concerning Guidelines for Hostage Taking and Rehabilitation of the Reputation of Taxpayers Hostage. Tax bearers who have been taken as hostages have fully paid their tax debts which have resulted in increased tax revenues and coordination with related agencies so that hostage-taking (gijzeling) is an effort to enforce the law. in optimizing tax revenue can be implemented properly